(untitled) (Bangladesh Journal of Zoology, 2010)
Trial on tilapia, (Oreochromis niloticus) culture in low cost bamboo framed one cubic meter net cages was performed in six villages of Matlab upzila, Chandpur from July to November 2005. In total 20 poor women were selected through an NGO. They were provided with two days training on culture and management, cage materials, tilapia fries (250 per cage) and fish food for one month. The women used kitchen wastes and plant supplements as tilapia’s food. After 120 days of stocking, the results showed that the final production of fishes in cages under two cycle varied from 64.9 kg to 142.93 kg. Considering the nine ponds in six villages the maximum production was observed in the pond at Gozra village (average production 47.64 ± 0.32 kg) where three cages were installed followed by the pond at village Pachani (average production 42.52 ± 0.50 kg) for two cages. The lowest production was found in two ponds at village Balurchar (18.02 ± 0.59 kg). The production was significantly varied among cages (F=42.723, P≤ 0.00) and as well as among villages (F=-57.140, P≤ 0.00). This was due to the variation of survival (F= 10.989, P≤ 0.00) and daily growth (F= 28.259; P≤ 0.00) of fish in cages. Pond size, management effort and public interest can differ village to village. These factors alone or collectively influence upon the specific growth rate, harvested fish number and production of fishes in cages. In small scale pond cage tilapia culture, the loss of production was due to the poor management practice by the owner. It is evident from the study that tilapia culture in cages is a suitable technology for an additional income source for rural women for the improvement of their livelihoods and household nutrition in these villages. Bangladesh J. Zool. 38(1): 133-142, 2010